PERGESERAN NILAI DAN FUNGSI TURUK LAGGAI PADA MASYARAKAT DESA TUAPEJAT KECAMATAN SIPORA UTARA KABUPATEN KEPULAUAN MENTAWAI SUMATERA BARAT - Yulianti, Devita; Oktavia, Dian Anggraini; Rahmad, Darmairal (Pendidikan Sosiologi, 2013)
Turuk laggai a village dance is full of symbols. First turuk laggai symbolize about animal life activities, for the treatment of ceremonies, and feasts Mentawai. Now turuk laggai besides symbolize about the activities of animal life also symbolized the social life of the community about the activities of a ceremonial nature. The problems of this research are: 1) What is the meaning turuk laggai, 2) What shape shifting value and function turuk laggai, 3) What factors are causing a shift in values and functions turuk laggai, 4) How does the existence of the villagers turuk laggai Tuapejat subdistrict North Sipora Mentawai Islands. The purpose of this study is to understand the meaning contained in turuk laggai, describe the form and function of the value shift turuk laggai, analyzing the factors that cause a shift in values and fngsi turuk laggai, as well as the existence turuk laggai currently in the village of North Sipora Sub Tuapejat Mentawai Islands. The type of data in the form of qualitative research using descriptive methods. The technique used for data collection are observation, interviews and document research. Informants in this study set out intentionally (purposive sampling), which consists of 22 indigenous people living in the Mentawai Tuapejat. Results of this study revealed that turuk laggai a village dance that has artistic value, sacred and mystical, which is held at each ceremony. Turuk laggai divided into two parts, namely: 1) Turuk sikerei is sacred and mystic, who works for the ceremony and punen pulaggengan kamateiat, 2) turuk simata is turuk that is entertaining, which serves to show punen putalimaugat. Shape shifting value and function turuk laggai is the loss of traditional ceremonies that use turuk laggai that are sacred and mystical, so turuk laggai only used for ceremonial rituals that are fun. Contributing factor is religion, government, technology, education, natural and economic conditions. While the existence of the villagers turuk laggai Tuapejat manifested in the form of management of Studio Team Ogok Laggai administered by the Department of Tourism Culture and Sport, held in the form of ceremonial occasions.